Green's functions : - Melnikov, Yu. A. (De Gruyter, 2012)
This monograph is looking at applied elliptic and parabolic type partial differential equations in two variables. The elliptic type includes the Laplace, static Klein-Gordon and biharmonic equation. The parabolic type is represented by the classical heat equation and the Black-Scholes equation which has emerged as a mathematical model in financial mathematics. The book is attractive for practical needs: It contains many easily computable or computer friendly representations of Green's functions,includes all the standard Green's functions andmany novel ones, and provides innovative and new approaches that might lead to Green's functions